How Millennials Assess the Usability of E-Wallets - Wati, Ina Kartika; Soma, A M; Ispriyahadi, Heri (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2024)
This study investigates the impact of internet and technological advancements on millennials (born between 1981 and 2000), particularly focusing on their adoption of digital payment systems, notably the DANA platform. It examines whether millennial satisfaction with digital payment services, amidst FOMO trends, influences their loyalty to the platform. This research utilizes quantitative methods and Smart PLS for analysis with 108 millennial participants, emphasizing gender distribution and age range. The results indicate a significant correlation between electronic satisfaction (E-satisfaction) and electronic loyalty (E-Loyalty) among users, suggesting that higher satisfaction leads to increased loyalty. These findings highlight the platform's sustainability amid evolving millennial behaviors and FOMO trends, offering valuable insights into consumer dynamics and digital payment platforms' success.